2014
DOI: 10.2478/s11536-013-0335-6
|View full text |Cite
|
Sign up to set email alerts
|

Markers of inflammation and microvascular complications in type 1 diabetes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Although there is an evidence of increased IL-6 serum levels in T1DM patients with developed DN [103], others have found that they do not differ in regard to levels in patients without DN [104]. As far as DR is concerned, some studies report higher serum levels of IL-6 in T1DM patients with developed DR [105,106], while other investigators have found differences only in case of considering different degrees of retinopathy [104], and the third have concluded that there is no correlation between IL-6 serum level and DR [102]. One of the studies has demonstrated the correlation of increased IL-6 serum levels and autonomic neuropathy [107], while other has not found the difference in serum levels of IL-6 between T1DM patients without and with developed DNP [104].…”
Section: Interleukin-6 and Chronic Complications Of Type 1 Diabetesmentioning
confidence: 96%
See 2 more Smart Citations
“…Although there is an evidence of increased IL-6 serum levels in T1DM patients with developed DN [103], others have found that they do not differ in regard to levels in patients without DN [104]. As far as DR is concerned, some studies report higher serum levels of IL-6 in T1DM patients with developed DR [105,106], while other investigators have found differences only in case of considering different degrees of retinopathy [104], and the third have concluded that there is no correlation between IL-6 serum level and DR [102]. One of the studies has demonstrated the correlation of increased IL-6 serum levels and autonomic neuropathy [107], while other has not found the difference in serum levels of IL-6 between T1DM patients without and with developed DNP [104].…”
Section: Interleukin-6 and Chronic Complications Of Type 1 Diabetesmentioning
confidence: 96%
“…Most of the studies analyzing the serum levels of IL-6 in T1DM have concluded that they are higher in the patients compared to the ones in nondiabetic subjects [96][97][98][99][100], while some of the investigators have found that levels are similar in two groups [101,102]. Although there is an evidence of increased IL-6 serum levels in T1DM patients with developed DN [103], others have found that they do not differ in regard to levels in patients without DN [104]. As far as DR is concerned, some studies report higher serum levels of IL-6 in T1DM patients with developed DR [105,106], while other investigators have found differences only in case of considering different degrees of retinopathy [104], and the third have concluded that there is no correlation between IL-6 serum level and DR [102].…”
Section: Interleukin-6 and Chronic Complications Of Type 1 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes has become a common disease in modern society. It is a chronic disease in which blood glucose concentration fluctuates from its normal range (90-140mg/dl) causing a significant impact on health [1][2]. According to a study made by the International Diabetes Federation (IDF) in 2014, 387 million people had diabetes; by 2035 this will rise to 600 million [3].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes has become a common disease in modern society. The blood glucose is too high or too low both will cause a significant impact on health, and the complications of diabetes are very serious, such as liver cirrhosis and neuropathy (Garcia-Compean et al 2009, Mitrović et al 2014 [1] [2]. Diabetes is a disease difficult to cure, only through diet or insulin injections to control blood glucose.…”
Section: Introductionmentioning
confidence: 99%